2021
DOI: 10.3390/jcm10235699
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rehabilitative Ultrasound Imaging Technique in the Lumbopelvic Region as a Diagnosis and Treatment Tool in Physiotherapy: Systematic Review, Meta-Analysis and Meta-Regression

Abstract: Rehabilitative ultrasound imaging (RUSI) technique seems to be a valid and reliable tool for diagnosis and treatment in physiotherapy and has been widely studied in the lumbopelvic region the last three decades. The aims for this utility in clinical settings must be review through a systematic review, meta-analysis and meta-regression. A systematic review was designed following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines with PROSPERO registration and per review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…The RUSI technique presented several benefits for musculoskeletal soft tissue assessments, including joints, tendons, nerves and muscles [ 15 , 16 ]. Concretely, a recent systematic review with meta-analysis and meta-regression revealed that RUSI provided high reliability and validity measurements, especially in the lumbopelvic region, claiming promising findings for diagnostic and intervention evaluations in the physical therapy and rehabilitation fields [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RUSI technique presented several benefits for musculoskeletal soft tissue assessments, including joints, tendons, nerves and muscles [ 15 , 16 ]. Concretely, a recent systematic review with meta-analysis and meta-regression revealed that RUSI provided high reliability and validity measurements, especially in the lumbopelvic region, claiming promising findings for diagnostic and intervention evaluations in the physical therapy and rehabilitation fields [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the LPP condition was linked to greater diaphragm fatigability [ 28 ], reduced excursion and a higher diaphragmatic dome position [ 29 ]. Nevertheless, ultrasonography tools were cheaper and more portable compared to MRI devices, providing clear reasons for the increased use of the RUSI technique in physical therapy and rehabilitation [ 13 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasound in physiotherapy as a musculoskeletal assessment has increased [ 34 , 35 ] last decades, and in this study, we verified in an analytical and isolated way the decrease in thickness both in contraction and at rest ( Table 3 ) of the anterior rectus of the quadriceps of the subjects operated on for ACL.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, processes are successful in 46 non-randomized trials including external or internal fixation in 1,519 people showed no useful results. 9,10 In addition to the lack of majority rule over the older more experienced approaches. In addition, no prospective randomised or high-quality non-randomized research has yet been performed on the most popular ideas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no prospective randomised or high-quality non-randomized research has yet been performed on the most popular ideas. 9,10 Four systematic research studies have compared basic reduction and internal fixation to locked or direct reduction, even as it is acquainted. The data has demonstrated that a good finding has been originating from an inner obsession.…”
Section: Discussionmentioning
confidence: 99%